From Oral Legend to Written Story: Traditional Stories in Santa Martha Acatitla (Andamios, Revista de Investigación Social, 2025)
This paper takes as its starting point one of the distinguishing characteristics of legends: truth value, to reflect on whether this value is intrinsic to the story or extrinsic to it. The object of study is the stories collected through both archival and field work in Santa Martha Acatitla. In both cases, we observe how the transmitter alters the narrative’s point of view, thereby shifting its truth value as it transitions from oral to written tradition. In this way, stories that were known as legends become tales. We discuss some of the factors that provoke this change. We consider not only the narrator’s shift in focus when the story is translated into writing, but also the local social context in which it is set.
Keywords: Traditional legend; tale; oral tradition; written tradition; Santa Martha Acatitla; penitentiary